2012
DOI: 10.5754/hge12071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Smac and Ki-67 Expression in Pancreatic Cancer

Abstract: The higher expression of Smac and Ki-67 appear to play a role in the pathogenesis of pancreatic cancer. Combined detection of these proteins may improve the prognostic evaluation of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 0 publications
3
30
0
1
Order By: Relevance
“…Second, the expression levels of Ki-67 and caspase-3 were correlated with the grading of NET. This finding was consistent with that of previous studies showing that the expression levels of Ki-67 and caspase-3 were correlated with the occurrence and development of cancer (Deniz et al, 2015;Hu et al, 2012). Third, the expression levels of Ki-67 decreased and those of caspase-3 increased after everolimus treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, the expression levels of Ki-67 and caspase-3 were correlated with the grading of NET. This finding was consistent with that of previous studies showing that the expression levels of Ki-67 and caspase-3 were correlated with the occurrence and development of cancer (Deniz et al, 2015;Hu et al, 2012). Third, the expression levels of Ki-67 decreased and those of caspase-3 increased after everolimus treatment.…”
Section: Discussionsupporting
confidence: 92%
“…However, the molecular mechanism underlying the pathogenesis of NET remains to be further explored. Studies showed that the expression of Ki-67 and caspase-3 was closely correlated with the occurrence and development of breast (Deniz et al, 2015) and pancreatic cancers (Hu et al, 2012). However, the expression profiles and roles of Ki-67 and caspase-3 in NET remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Expression is noted also in phases G 1 , S and M, but no expression is found in phase G 0 [29]. Ki-67 expression correlates with the tumour grade and lymph node metastasis [29]. It has also been stated that the expression of Ki-67 becomes prognostically significant if it exceeds 5% [6,7].…”
Section: Discussionmentioning
confidence: 98%
“…The highest expression of this protein is in G 2 phase of proliferative cells. Expression is noted also in phases G 1 , S and M, but no expression is found in phase G 0 [29]. Ki-67 expression correlates with the tumour grade and lymph node metastasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Ki67 was significantly more highly expressed in malignant than in normal tissues. [14,15] The nuclear proliferative antigen Ki67 is identified to correlate with the prognosis of the patients to predict the outcome and distant metastasis of sarcoma patients. A significant correlation has been reported between Ki67 expression and mitotic rate in sarcomas.…”
Section: Discussionmentioning
confidence: 99%